Antineuronal antibody prevalence in Alzheimer dementia: Development of new models and analysis methods/neuroinflammation. (7th December 2020) - Koertvelyessy, Peter; Teegen, Bianca; Stoecker, Winfried; Düzel, Emrah; Glanz, Wenzel; Bittner, Daniel; Vielhaber, Stefan; Diekaemper, Elena; Pruess, Harald
Abstract: Background: The prevalence of antibodies against neuronal epitopes (nAB) in CSF and serum of Alzheimer dementia (AD) patients is unknown, as is the potential contribution to pathomechanisms influencing the clinical picture parallel to neurodegeneration. Method: We screened CSF and serum of 164 AD patients and 29 control patients suffering from depression with cognitive impairment. 36 known nAB were examined using cell‐based immunoassays (EUROIMMUN, Germany). Every sample was also examined for as yet undefined nAB using native brain slices of hippocampus and cerebellum. We compared standard CSF parameters and biomarkers of neurodegeneration (commercial ELISA kits, Fujirebio, Ghent, Belgium) between nAB‐positive and negative AD patients and controls. A pathological finding is defined for each nAB reaching or exceeding a predefined, known titer and having a corresponding binding pattern as seen on native hippocampus and/or cerebellum. Result: We found nAB in 20.1% (33/164) of the AD patients' serum with 1.8% (3/164) having pathological findings (1*IgG NMDAR, 1*Homer3 and 1*GABAbR antibodies). 2 AD patients had the same nAB in CSF and serum, no nAB was found in CSF alone. Three out of the 29 control patients had nABs but noone had pathological titers. There was no difference between nAB‐positive and nAB‐negative AD and controls regarding the biomarkers and standard CSF parameters in one‐way ANOVA (see Figure 1 for details and Figure 2 as an overview). Clinical records of the 3 nAB‐positive AD patients with pathological findings showed normal CSF parameters and biomarkers without signs of abnormal neurological findings with a mean follow‐up of 37 months (ranging from 14‐54 months). Conclusion: This is the largest study on nAB prevalence in AD using the largest nAB panel so far. In general, prevalence of nABs is high in AD patients. Three patients out of all 193 patients (AD+controls) had pathological nAB findings. Follow‐up of the medical records over more than three years did not reveal aberrant clinical courses. CSF parameters and biomarkers of neurodegeneration did not show any difference between nAB‐positive and ‐negative patients. Patients were not treated with immunosuppressive therapy and therefore the potential impact of the nAB on the clinical picture will require further studies.